Demographic Differences in Circumcision Satisfaction among U.S. Males - Sardi, Lauren; Jellison, William (Archives of Men’s Health, 2021)
Introduction: Male circumcision involves the partial or total removal of the prepuce (foreskin) from the penis, and it is the most common surgical procedure performed on infants in the USA. According to social convention theory, in demographic populations where male circumcision is more socially accepted, we would predict that circumcised men would be more likely to report satisfaction with their circumcision status. This exploratory study investigated the ways in which particular demographic sub-groups have differing attitudes and levels of satisfaction based on their circumcision status. Materials and Methods: The participant data used in these analyses are from a study conducted to explore the effects of false beliefs concerning circumcision and intact penises on circumcision satisfaction. After participant exclusion based on additional criteria, 902 male participants from the United States, ranging in age from 18-75 (M = 34.0, SD = 10.0), remained. A series of demographic information by circumcision status between participants Analysis of Variances (ANOVA) were conducted on circumcision status satisfaction. Results: Results indicated that circumcision status satisfaction varied as a function of race/ethnicity, religion, relationship status, and sexual orientation. Statistically significant differences in circumcision status satisfaction were found for all of the demographic variables. Conclusion: Using social convention theory, these data suggest that circumcision satisfaction is related to endorsement of the dominant culture and its norms surrounding the masculine body. Further investigation is warranted regarding causal implications of how one’s demographic characteristics may affect one’s satisfaction with their circumcision status.